Hypoxylonol F Isolated from Annulohypoxylon annulatum Improves Insulin Secretion by Regulating Pancreatic beta-cell Metabolism - Lee, Dahae; Hwang, Buyng Su; Choi, Pilju; Kim, Taejung; Kim, Youngseok; Song, Bong Geun; Yamabe, Noriko; Hwang, Gwi Seo; Kang, Ki Sung; Ham, Jungyeob (MDPI, 2019)
Insulin plays a key role in glucose homeostasis and is hence used to treat hyperglycemia, the main characteristic of diabetes mellitus. Annulohypoxylon annulatum is an inedible ball-shaped wood-rotting fungus, and hypoxylon F is one of the major compounds of A. annulatum. The aim of this study is to evaluate the effects of hypoxylonol F isolated from A. annulatum on insulin secretion in INS-1 pancreatic beta-cells and demonstrate the molecular mechanisms involved. Glucose-stimulated insulin secretion (GSIS) values were evaluated using a rat insulin ELISA kit. Moreover, the expression of proteins related to pancreatic beta-cell metabolism and insulin secretion was evaluated using Western blotting. Hypoxylonol F isolated from A. annulatum was found to significantly enhance glucose-stimulated insulin secretion without inducing cytotoxicity. Additionally, hypoxylonol F enhanced insulin receptor substrate-2 (IRS-2) levels and activated the phosphatidylinositol 3-kinase/protein kinase B (PI3K/Akt) pathway. Interestingly, it also modulated the expression of peroxisome proliferator-activated receptor gamma (PPAR gamma) and pancreatic and duodenal homeobox 1 (PDX-1). Our findings showed that A. annulatum and its bioactive compounds are capable of improving insulin secretion by pancreatic beta-cells. This suggests that A. annulatum can be used as a therapeutic agent to treat diabetes.
Keywords: GLUCOSE; PIOGLITAZONE; METFORMIN; SAFETY; RISK; PDX1; MASS